Integrasi Joyful Learning dalam Project-Based Learning untuk Meningkatkan Kemampuan Numerasi - Elis Nurhayati (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2026)
Low students’ numeracy ability remains a significant issue in learning, which is partly caused by limited active engagement and less engaging learning environments. The integration of the Joyful Learning approach within the Project-Based Learning (PjBL) model offers an alternative solution by creating interactive, enjoyable, and meaningful learning experiences throughout project-based learning stages. This study employed a quasi-experimental method with a nonequivalent control group design involving experimental and control groups. The subjects consisted of three schools, each comprising two classes. Data were collected through numeracy tests (pretest and posttest). The results showed that the average numeracy ability of students in the experimental class increased from 38.63 to 77.63, while the control class increased from 36.49 to 62.94. The improvement in the experimental class was consistently higher than that of the control class across all schools. Overall, the N-gain score in the experimental class was in the medium to high category with an average of 0.64, whereas the control class was in the medium category with a score of 0.42. Specifically, the N-gain values in the experimental class were 0.69 (School A), 0.61 (School B), and 0.60 (School C), which were higher than those of the control class, namely 0.55, 0.37, and 0.33. These findings indicate that the integration of Joyful Learning within Project-Based Learning is effective in improving students’ numeracy skills and can serve as an innovative instructional strategy in mathematics learning.